The polychrome wood interiors, its history & characteristics through the Aleppine Ottoman Houses, Syria - Alafandi, Rami; Abdul Rahim, Asiah (Global Research and Development Services, 2017)
The objective of this paper is to show the importance of the Polychrome wooden interior of Aleppine houses. Aleppo is the second largest city in Syria (after the capital Damascus) and is the commercial capital of Syria. Aleppo has a long history, extending from the third millennium B.C to the Islamic era. Islamic rulers made Aleppo great by re-building its walls, gates, towers and citadel. The Muslims also built mosques, schools, houses, inns, markets, hospitals, bathhouses, and public facilities. Consequently, Aleppo flourished and became an important station on the Silk Road; the third largest city in the Ottoman Empire after Istanbul and Cairo. Aleppo was part of the Ottoman Empire from 1516 to 1918. As part of this empire, local Aleppine architects and artisans combined their techniques and cultural heritage with the other parts of the Ottoman Empire. Due to growth in population, the Ottomans developed and expanded the city, provided facilities, and established more neighborhoods outside of the walls. The polychrome wooden decorations flourished in the Ottoman era in Syria to decorate the wealthy houses by talented craftsmen. The polychrome wooden decorations called ‘ajami by the Syrian craftsmen. The workshops of ‘ajami have implemented many houses in Damascus, Hama and Aleppo. Syrian and especially Damascene craftsmen became known by this art and called Damascene painting beside ‘ajami. This research employs a historical and descriptive approach to explore the history, design and styles of the ‘ajami during the Ottoman period. Since 2012, much of Syria’s architectural heritage has been destroyed due to the conflict. In Aleppo, the losses in both ancient and modern parts of the city have been tremendous. Some traditional houses have been damaged. This paper will highlight the current situation of the ‘ajami in the Aleppine houses.